Forecasting the influence of conservation strategies on landscape connectivity. Issue 5 (23rd June 2022) - Mozelewski, Tina G.; Robbins, Zachary J.; Scheller, Robert M.
Abstract: Maintaining and enhancing landscape connectivity reduces biodiversity declines due to habitat fragmentation. Uncertainty remains, however, about the effectiveness of conservation for enhancing connectivity for multiple species on dynamic landscapes, especially over long time horizons. We forecasted landscape connectivity from 2020 to 2100 under four common conservation land‐acquisition strategies: acquiring the lowest cost land, acquiring land clustered around already established conservation areas, acquiring land with high geodiversity characteristics, and acquiring land opportunistically. We used graph theoretic metrics to quantify landscape connectivity across these four strategies, evaluating connectivity for four ecologically relevant species guilds that represent endpoints along a spectrum of vagility and habitat specificity: long‐ versus short‐distance dispersal ability and habitat specialists versus generalists. We applied our method to central North Carolina and incorporated landscape dynamics, including forest growth, succession, disturbance, and management. Landscape connectivity improved for specialist species under all conservation strategies employed, although increases were highly variable across strategies. For generalist species, connectivity improvements were negligible. Overall, clustering the development of new protected areas around land already designated for conservation yielded the largest improvements in connectivity; increases were several orders of magnitude beyond current landscape connectivity for long‐ and short‐distance dispersing specialist species. Conserving the lowest cost land contributed the least to connectivity. Our approach provides insight into the connectivity contributions of a suite of conservation alternatives prior to on‐the‐ground implementation and, therefore, can inform connectivity planning to maximize conservation benefit. Abstract : Pronóstico de la Influencia de las Estrategias de Conservación sobre la Conectividad del Paisaje Resumen: El mantenimiento y la mejora de la conectividad de paisaje reduce las declinaciones de biodiversidad causadas por la fragmentación del hábitat. Sin embargo, todavía existe incertidumbre sobre lo efectiva que es la conservación para la mejora de la conectividad para múltiples especies en paisajes dinámicos, especialmente durante periodos largos. Pronosticamos la conectividad de paisaje desde el 2020 hasta el 2100 bajo cuatro estrategias comunes de adquisición de tierras para conservación: adquisición de las tierras más baratas, adquisición de conjuntos de tierras adyacentes a áreas de conservación ya establecidas, adquisición de tierras con una gran diversidad de características geográficas, y adquisición oportunista de tierras. Después usamos medidas de teoría de grafos para cuantificar la conectividad de paisaje en estas cuatro estrategias y para evaluar la conectividad de cuatro gremios de especies con relevancia ecológica que representan los puntos finales en un espectro de movilidad y especificidad de hábitat: habilidad de dispersión de distancia corta versus larga y especialistas versus generalistas de hábitat. Aplicamos nuestro método en el centro de Carolina del Norte e incorporamos las dinámicas de paisaje, incluyendo el crecimiento, sucesión, alteración y gestión forestales. La conectividad del paisaje mejoró para las especies especialistas bajo todas las estrategias de conservación que se usaron, aunque los incrementos fueron muy variables según la estrategia. Para las especies generalistas, las mejoras en la conectividad fueron insignificantes. En general, agrupar al desarrollo de nuevas áreas protegidas alrededor de tierras ya designadas a la conservación produjo la mayor cantidad de mejoras en la conectividad; los incrementos estuvieron varias magnitudes más allá de la conectividad actual del paisaje para las especies especialistas con dispersión de corta y larga distancia. La conservación de las tierras más baratas contribuyó a la menor conectividad. Nuestra estrategia proporciona información sobre las contribuciones de conectividad de un conjunto de alternativas de conservación previas la implementación in situ y por lo tanto puede servir para orientar la planeación y maximizar el beneficio de conservación. 预测保护策略对景观连接度的影响: 【摘要】维持和提高景观连接度可以减少因生境破碎化导致的生物多样性丧失。然而, 在动态的景观中提高多物种连接度的保护有效性仍存在不确定性, 特别是在较长的时间范围内。本研究预测了 4 种常见的保护性土地征用策略在 2020 年到 2100 年的景观连接度, 这些策略包括征用成本最低的土地、征用已有保护区周围的土地、征用地理多样性高的土地, 以及随机征用土地。我们使用图论指标量化了这 4 种策略的景观连接度, 评估了 4 个有生态价值的物种种群的连接度, 这些物种代表了不同的扩散能力和栖息地特异性:从长距离扩散到短距离扩散, 以及从栖息地专性种到广适种。我们将该方法应用于北卡罗来纳州中部, 并纳入了景观动态, 包括森林生长、演替、干扰和管理。我们发现, 专性种的景观连接度在所有保护策略下都得到了改善, 尽管不同策略之间的效果存在差异。而广适种的连接度则几乎没有提高。总的来说, 将新的保护区集中在已经建立的保护地周围, 可以最大限度地提高连接度;长距离和短距离扩散的专性种连接度的增加比目前的景观连接度要高出几个数量级。保护成本最低的土地对连接度的贡献最小。我们的方法为一系列保护替代方案实施前的连接度贡献评估提供了见解, 因此可以为连接度规划提供信息, 使保护效益最大化。【翻译: 胡怡思; 审校: 聂永刚】